A nuclear target sequence capture probe set for phylogeny reconstruction of the charismatic plant family Bignoniaceae - Fonseca, Luiz Henrique M.; Carlsen, Mónica M.; Fine, Paul V. A.; Lohmann, Lúcia G. (Frontiers in Genetics, 2023)
The plant family Bignoniaceae is a conspicuous and charismatic element of the tropical flora. The family has a complex taxonomic history, with substantial changes in the classification of the group during the past two centuries. Recent re-classifications at the tribal and generic levels have been largely possible by the availability of molecular phylogenies reconstructed using Sanger sequencing data. However, our complete understanding of the systematics, evolution, and biogeography of the family remains incomplete, especially due to the low resolution and support of different portions of the Bignoniaceae phylogeny. To overcome these limitations and increase the amount of molecular data available for phylogeny reconstruction within this plant family, we developed a bait kit targeting 762 nuclear genes, including 329 genes selected specifically for the Bignoniaceae; 348 genes obtained from the Angiosperms353 with baits designed specifically for the family; and, 85 low-copy genes of known function. On average, 77.4% of the reads mapped to the targets, and 755 genes were obtained per species. After removing genes with putative paralogs, 677 loci were used for phylogenetic analyses. On-target genes were compared and combined in the Exon-Only dataset, and on-target + off-target regions were combined in the Supercontig dataset. We tested the performance of the bait kit at different taxonomic levels, from family to species-level, using 38 specimens of 36 different species of Bignoniaceae, representing: (i) six (out of eight) tribal level-clades (e.g., Bignonieae, Oroxyleae, Tabebuia Alliance, Paleotropical Clade, Tecomeae, and Jacarandeae), only Tourrettieae and Catalpeae were not sampled; (ii) all 20 genera of Bignonieae; (iii) seven (out of nine) species of Dolichandra (e.g., D. chodatii, D. cynanchoides, D. dentata, D. hispida, D. quadrivalvis, D. uncata, and D. uniguis-cati), only D. steyermarkii and D. unguiculata were not sampled; and (iv) three individuals of Dolichandra unguis-cati. Our data reconstructed a well-supported phylogeny of the Bignoniaceae at different taxonomic scales, opening new perspectives for a comprehensive phylogenetic framework for the family as a whole.